Penatausahaan Barang Milik Daerah Pada Dinas Perumahan Kawasan Permukiman dan Pertanahan Kabupaten Toraja Utara - Daniel Sari Patontongan; Frida Chairunisa; Nuraeni Sayuti (Politeknik STIA LAN Makassar, 2020)
The administration of regional property at the Housing Area, Settlement and Land Service Office of North Toraja Regency is still not going well, where assets are moving from room to room so their whereabouts are not known. The purpose of this research is to find out how the Administration of Regional Property in the Housing and Land Service of North Toraja Regency. The research approach used is a qualitative approach. The number of informants in this study were 10 people. The results of the study (1) bookkeeping still uses a manual system, there are still BMD that are not well recorded and are often late in doing bookkeeping; (2) The inventory of goods belonging to the regions does not have an item code label, does not have a recap list of goods and does not have inventory cards of goods in each room; (3) reporting is often late due to lack of discipline in the management of goods in making reports and (4) inadequate human resources for goods managers, goods managers have never attended or received training related to BMD administration. Keywords : Management of BMD, Bookkeeping, Inventory, Reporting.